2017
DOI: 10.4103/0378-6323.191132
|View full text |Cite|
|
Sign up to set email alerts
|

Neurological diseases and bullous pemphigoid: A case–control study in Iranian patients

Abstract: Neurological diseases in general, and stroke and dementia in particular, were significantly associated with bullous pemphigoid in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The frequency of neurological diseases in their case group was 26.3%. They noted that stroke (17.5%) and dementia (5.6%) were significantly associated with BP [37]. …”
Section: Discussionmentioning
confidence: 99%
“…The frequency of neurological diseases in their case group was 26.3%. They noted that stroke (17.5%) and dementia (5.6%) were significantly associated with BP [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study including a larger sample of BP patients, Khosravani et al reported no difference between BP patients and controls in terms of MS. Nevertheless, MS has been linked to BP in multiple studies 16,18,22,24 . On the other hand, the risk of Parkinson's disease appears to be higher in BP patients, 22 yet we were not able to evaluate its pattern in our study.…”
Section: Discussionmentioning
confidence: 73%
“…Some studies have shown a higher likelihood of both stroke and dementia in BP patients. [15][16][17][18] On the contrary, some researchers have demonstrated similar dementia rates in BP patients and controls. 10,[19][20][21] We did not observe Alzheimer MRI patterns in these patients, nor did we find such pattern in the control group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The range of age between 80 and 89 years showed the highest association with neuropsychiatric diseases. In the literature, several studies have evaluated the association between mean age of patients with BP and neurological pathologies, showing that patients with neurological comorbidities were generally older than those without (34,39,40). This result may be explained by the concept of immuno-senescence that is an age-related immune dysfunction with a consequent process of autoimmunization against antigens common between the CNS and epidermis (39).…”
Section: Discussionmentioning
confidence: 99%